Characteristics of microstructure and stresses and their effects on interfacial fracture behavior for laser-deposited maraging steel. (5th January 2018) - Wei, Shaopeng; Wang, Gang; Wang, Liping; Rong, Yiming
Abstract: Laser cladding is one of the most attractive ways to repair or remanufacture high-added-value engineering components. The present paper describes the effect of microstructure and residual stresses on the interfacial fracture behavior of laser-deposited maraging steel. The multi-layer overlapped cladding material was deposited on maraging steel substrates using laser hot-wire deposition. Residual stress profile was measured by X-ray diffraction. Temperature evolution and the induced phase transformation during the process were investigated to reveal the generation mechanism of residual stresses. A novel testing method was developed to analyze the interfacial fracture behavior and evaluate the bonding strength with specially designed T-shaped samples. The compressive stresses derived from martensitic expansion was presented in the clad layer, and tensile stresses in the heat affected zone up to a depth of 4 mm, which was caused by thermal shrinkage. Both the solidification micro-voids and steep stress gradient appearing in the interface contributed to the propagation of interfacial crack that will critically affect the mechanical properties of laser deposited material. Graphical abstract: Highlights: Compressive stress existed in clad layer, and tensile in HAZ with a depth of 4 mm. Stress profile resulted from interaction between thermal shrinkage and martensitic expansion. Fracture morphology presents recognizable boundaries along laser scanning direction. Solidification voids and steep stress gradient facilitated interfacial crack propagation.